2010
DOI: 10.2527/jas.2009-2259
|View full text |Cite
|
Sign up to set email alerts
|

Oral inoculation with Salmonella enterica serovar Typhimurium or Choleraesuis promotes divergent responses in the somatotropic growth axis of swine1

Abstract: Enteric disease and immune challenge are processes that have detrimental effects on the growth performance of young swine. The current study tested the hypothesis that salmonella-induced enteric disease would perturb the endocrine growth axis in a serovar-dependent fashion. Specifically, we evaluated the effects of Salmonella enterica serovar Typhimurium (Typhimurium) and serovar Choleraesuis (Choleraesuis) on critical regulatory components of growth in young swine. Weaned pigs were housed 2 per pen with ad li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…However, in this study the ST inoculation doses evaluated did not increase rectal temperature even with most animals excreting ST in the first week post-infection. The same results were reported by Davis et al [ 25 ] in younger pigs inoculated with 10 8 CFU of ST in a 14 days trial. The authors did not observe any differences in the rectal temperature of ST-inoculated pigs even when three doses were given at three different times.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…However, in this study the ST inoculation doses evaluated did not increase rectal temperature even with most animals excreting ST in the first week post-infection. The same results were reported by Davis et al [ 25 ] in younger pigs inoculated with 10 8 CFU of ST in a 14 days trial. The authors did not observe any differences in the rectal temperature of ST-inoculated pigs even when three doses were given at three different times.…”
Section: Discussionsupporting
confidence: 89%
“…The dose administration of 1 × 10 8 and 1.5 × 10 8 CFU in this study were chosen to more closely mimic the fecal–oral transmission of Salmonella organisms often found in intensive swine production conditions, as it was previously reported that growing–finishing phase pigs could shed high concentrations of ST in the environment (between 10 6 and 10 8 CFU/g of feces) [ 12 , 13 ]. Additionally, studies in which pigs were inoculated with doses between 10 6 and 10 7 showed the presence of mild infections or had no different outcomes from no-challenge animals [ 24 , 25 ]. Furthermore, when pigs were inoculated with higher doses of Salmonella Typhimurium (10 9 CFU) severe clinical responses and mortality were observed [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to Shurson & Johnston (1998), the increase of tissue catabolism after activation of the immune system can be related to this process. Moreover, another likely explanation is the reduction of serum IGF-I (insulin-like growth factor type I), according to what was observed by Davis et al (2010). These authors inoculated orally Salmonella in pigs in the initial phase and observed reduction in the weight gain of the animals.…”
Section: Resultsmentioning
confidence: 66%
“…The top five tissues with the highest expression level were the liver, spleen, brain, gill, and head kidney. In humans, IGFBP5 was closely related to many diseases, such as colorectal cancer, chronic rhinosinusitis, sarcopenia, and so on ( 51 – 55 ), and pathogen infection induced a significantly higher expression of IGFBP5 in mammals—for example, IGFBP5 expression was significantly upregulated after Salmonella enterica stimulation in pigs ( 56 ). In our study, V. harveyi caused a significant induction of TroIGFBP5b in the liver, spleen, and head kidney.…”
Section: Discussionmentioning
confidence: 99%